Treatment Choices for Tenosynovial Giant Cell Tumor: Surgery or Observation? - Xu, Hairong; Chen, Jing; Niu, Xiaohui (Zhongliu fangzhi yanjiu, 2025)
Tenosynovial giant cell tumor (TGCT) is a rare mesenchymal tumor that clinically presents as nodular-type or diffuse-type (D-TGCT). D-TGCT is more aggressive, has a higher surgical recurrence rate, and can potentially lead to severe joint destruction. The traditional treatment is primarily through surgical intervention. Recent advancements in understanding the molecular mechanisms of the disease and the development of new drugs have significantly changed TGCT treatment strategies. Drug therapy and active surveillance have become important treatment options for unresectable or high-recurrence-risk TGCT. Imaging examinations and patient-reported outcome tools play a crucial role in evaluating efficacy and guiding treatment decisions. Comprehensive management by a multidisciplinary team and utilizing individualized treatment plans can significantly improve the quality of life and treatment outcomes of patients. Future research should explore the molecular mechanisms of TGCT, enhance multidisciplinary collaboration, and emphasize long-term management to improve treatment efficacy and patient prognosis.